Extraction of Valuable Metals From Spent Hydrodesulfurization Catalyst By Two Stage Leaching Method - T. Mohammed, Wadood; S. Ahmedzeki, Nada; F. AbdulNabi, Mariam (Iraqi Journal of Chemical and Petroleum Engineering, 2011)
Spent hydrodesulfurization (Co-Mo/γ-Al2O3) catalyst generally contains valuable metals like molybdenum (Mo), cobalt (Co), aluminium (Al) on a supporting material, such as γ-Al2O3. In the present study, a two stages alkali/acid leaching process was conducted to study leaching of cobalt, molybdenum and aluminium from Co-Mo/γ-Al2O3 catalyst. The acid leaching of spent catalyst, previously treated by alkali solution to remove molybdenum, yielded a solution rich in cobalt and aluminium.